Batch and fixed-bed adsorption of phosphate and nitrate on char derived by the co-pyrolysis of waste tires and corn cobs - Sally Ali Hussein; Muthanna Jabar Ahmed (International Journal of Renewable Energy Development, 2026)
The existence of both phosphorus (P) and nitrogen (N) in water can severely affect the aquatic environment by causing eutrophication phenomena. Co-pyrolysis has emerged as a viable thermal technology for converting various solid waste blends into extremely effective char. In this research, the co-pyrolysis of waste tires (WT) and corn cobs (CC) into char and its application as an adsorbent against nitrate and phosphate were investigated. The influence of various variables, including WT/CC blend composition, pyrolysis time, and pyrolysis temperature, on the performance and yield of char was also considered using batch and fixed-bed column tests. The characteristics of the obtained char were evaluated through Brunauer-Emmett-Teller analysis, Fourier transform infrared, and Field emission scanning electron microscopy with energy-dispersive X-ray analysis. Enhanced functioning and adsorption of pollutants were seen in the resulting material when the blend mixture was 25% WT + 75% CC. From the Sips isotherm, which exhibited high R2 values (0.9957, 0.9953) as compared to the Langmuir and the Freundlich isotherms, the maximum adsorption capacities of nitrate and phosphate were 59.19 and 77.23 mg/g, respectively. Two models, one for pseudo-second order and one for pseudo-first order, were used to examine the kinetic data, showing a strong adherence to the former model for the studied pollutants. Also, two popular fixed-bed adsorption models, the Yoon-Nelson and Thomas models, were utilized to match the adsorption data. Under varying circumstances, the findings agreed with the Yoon-Nelson and Thomas models, as measured by the correlation coefficient R2 values (0.8853-0.9946) for phosphate, (0.9463-0.9913) for nitrate, and (0.9658-0.9965) for phosphate, (0.8848-0.9966) for nitrate, respectively.